2019
DOI: 10.5603/gp.2019.0011
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of hr hPV E6/E7 mrna test in detecting cervical squamous intraepithelial lesion and cervical cancer

Abstract: Objectives: The paper assess the relevance of HR HPV E6/E7 mRNA test in women with abnormal Pap results. Material and methods: Between 2013-2014, 125 women were subjects to the enhanced diagnostics due to abnormal Pap results. According to The Bethesda system, if ASC-US, AGC, LSIL, ASC-H, HSIL or cancer cells were present, the result was abnormal. The patients underwent the enhanced diagnostics which included the following procedures: Pap smear collection for molecular assessment of HR HPV E6/E7 mRNA test, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The detection rate of HSIL + in the HPV16 group was 48.4%, which was signi cantly higher than that of the 18.8% in the HPV18/45 + group; that is, the highgrade (HSIL+) morbidity of HPV16/18/45 to the cervix was signi cantly higher than that of the Other HR-HPV, while HPV16 was signi cantly higher than HPV18/45. Pruski et al [22] found that high-grade squamous intraepithelial lesions were closely related to the positive expression of HPV E6/E7 mRNA. HPV-16 is the most common genotype in CIN2 + lesions diagnosed by LSIL in Chinese women, while HPV-18 is the most common genotype in CIN1 lesions [23], which is basically consistent with this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The detection rate of HSIL + in the HPV16 group was 48.4%, which was signi cantly higher than that of the 18.8% in the HPV18/45 + group; that is, the highgrade (HSIL+) morbidity of HPV16/18/45 to the cervix was signi cantly higher than that of the Other HR-HPV, while HPV16 was signi cantly higher than HPV18/45. Pruski et al [22] found that high-grade squamous intraepithelial lesions were closely related to the positive expression of HPV E6/E7 mRNA. HPV-16 is the most common genotype in CIN2 + lesions diagnosed by LSIL in Chinese women, while HPV-18 is the most common genotype in CIN1 lesions [23], which is basically consistent with this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cytology techniques continue to evolve with the incorporation of automation, artificial intelligence, and ancillary molecular tests (such as HPV) that have improved test performance. 23 , 31 , 32 , 33 , 34 Likewise, endometrial cytology techniques are ripe for ancillary test development to enhance or replace manual cytomorphologic evaluation, but technology has yet to be developed or tested. For now, inter‐observer variability is a factor in the reading of endometrial cytology by pathologists and likely would require specialized training for those who would read this type of sample regularly.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies on the performance of HPV E6/E7 mRNA test in diagnosing cervical diseases. Some reports have suggested that HPV E6 / E7 mRNA test is more sensitive and speci c than the HPV NDA test [22][23][24]. It has also been suggested that the HPV E6/E7 mRNA test is only more speci c than the HPV DNA test,having no difference in sensitivity [25].…”
Section: Discussionmentioning
confidence: 99%